B-vitamins and metabolic syndrome in Mesoamerican children and their adult parents. Issue 14 (7th October 2021) - Villatoro-Santos, Claudia R; Ramirez-Zea, Manuel; Villamor, Eduardo
Abstract: Objective: To examine the associations between vitamins of the methionine-homocysteine (Hcys) cycle (B6, B12 and folate) and Hcys with metabolic syndrome (MetS) among Mesoamerican children and their adult parents. Design: We conducted a cross-sectional study. Exposures were plasma vitamins B6 and B12 concentrations, erythrocyte folate and plasma Hcys. In children, the outcome was a continuous metabolic risk score calculated through sex- and age standardisation of waist circumference, the homoeostatic model assessment for insulin resistance, mean arterial pressure (MAP), serum HDL-cholesterol and serum TAG. In parents, the outcome was the prevalence of MetS according to the Adult Treatment Panel III Criteria. We estimated mean differences in the metabolic risk score and prevalence ratios of MetS between quartiles of the exposures using multivariable-adjusted linear and Poisson regression models, respectively. Setting: Capital cities of Belize, Guatemala, El Salvador, the Dominican Republic, Honduras, Nicaragua, Panama, Costa Rica and Chiapas State in Mexico. Participants: In total, 237 school-aged children and 524 parents. Results: Among children, vitamin B12 was inversely associated with the metabolic risk score (quartiles 4–1 adjusted difference = –0·13; 95 % CI: –0·21, –0·04; P trend = 0·008) through MAP, HDL-cholesterol and TAG. In contrast, folate was positively associated with the metabolic risk score (quartiles 4–1 adjusted difference = 0·11; 95 % CI: 0·01, 0·20; P trend = 0·02). In adults, vitamin B6 was inversely associated with MetS prevalence, whereas vitamin B12 and folate were positively related to this outcome. Conclusions: Vitamins of the methionine-Hcys cycle are associated with MetS in different directions. The associations differ between children and adults.